2015
DOI: 10.1007/s12035-015-9494-6
|View full text |Cite
|
Sign up to set email alerts
|

Brain Insulin Administration Triggers Distinct Cognitive and Neurotrophic Responses in Young and Aged Rats

Abstract: Aging is a major risk factor for cognitive deficits and neurodegenerative disorders, and impaired brain insulin receptor (IR) signaling is mechanistically linked to these abnormalities. The main goal of this study was to investigate whether brain insulin infusions improve spatial memory in aged and young rats. Aged (24 months) and young (4 months) male Wistar rats were intracerebroventricularly injected with insulin (20 mU) or vehicle for five consecutive days. The animals were then assessed for spatial memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 35 publications
4
31
0
2
Order By: Relevance
“…The brain protein level of BDNF was also lower, when measured after 6 months of diet 26 . BDNF signals partially via the insulin receptor substrate-1, phosphatidylinositol 3-kinase, and Akt pathway, similar to insulin 27 , but there also is evidence that intracerebroventricular infusion of insulin increased BDNF protein level in the hippocampus of young (4 months) but not older (24 months) rats 28 and that insulin signaling is required for normal BDNF transport and hippocampal synaptogenesis 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The brain protein level of BDNF was also lower, when measured after 6 months of diet 26 . BDNF signals partially via the insulin receptor substrate-1, phosphatidylinositol 3-kinase, and Akt pathway, similar to insulin 27 , but there also is evidence that intracerebroventricular infusion of insulin increased BDNF protein level in the hippocampus of young (4 months) but not older (24 months) rats 28 and that insulin signaling is required for normal BDNF transport and hippocampal synaptogenesis 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, to our knowledge, the effect of insulin as a memory enhancer has been reported to be controversial (Clayson 1971; Schwarzberg et al 1989; Kopf and Baratti 1996, 1999; Kopf et al 1998; Moosavi et al 2006). Moreover although insulin produces changes in proliferation of new cells and synaptic molecular pathways in aged animals, it enhances memory only in young but not aged populations, suggesting that it may protect against neuronal loss, but may not reliably improve memory performance in aging (Haas et al 2015). IGF-1, to our knowledge, has not yet been found effective in enhancing memory in healthy conditions (Stern et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin signaling has also been shown to impact BDNF and antioxidant enzyme production. Animal studies have reported that central insulin signaling stimulates the expression of BDNF in hippocampal neurons, whereas brain insulin receptor dysfunction has been associated with decreased levels of BDNF . In addition, streptozotocin‐induced diabetes mellitus in rats leads to decreased synthesis of GPx and SOD, an effect that is reversed by the administration of insulin .…”
Section: Discussionmentioning
confidence: 99%